Influence of exercise commitment on exercise adherence among undergraduate students: Chain mediation role of health beliefs and exercise behavior - JinJin Ren; PengWei Song (PLoS ONE, 2025)
This study probed into the correlation between exercise commitment and adherence among undergraduate students and expounded on the mediating role of health beliefs and exercise behavior. A questionnaire-based survey involved 617 Chinese undergraduate students, comprising 240 males and 377 females. The results reveal a significant positive correlation between exercise commitment and adherence (p < 0.01). Health beliefs and exercise behavior serve as crucial mediators in this relationship. The mediation effect, which is 0.241, encompasses the individual and chain mediating effects of health beliefs and exercise behavior. The proportion of the total mediation effect attributed to each pathway is 69.7% (health beliefs), 17.4% (exercise behavior), and 12.9% (chain mediation effect). These findings offer valuable insights into enhancing exercise adherence among undergraduate students, underscoring the importance of fostering exercise commitment, cultivating health beliefs, and promoting exercise behavior. Moreover, the study provides both theoretical and practical implications for physical education reform and health promotion initiatives in universities. However, as the sample was drawn exclusively from university students in Guangxi Province, the generalizability of the findings is limited. Future studies should expand the sample scope to include a more diverse population.